2011
DOI: 10.1007/s11916-011-0181-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Pain in Small-fiber Neuropathy

Abstract: Small fiber neuropathy manifests in a variety of different diseases and often results in symptoms of burning pain, shooting pain, allodynia, and hyperesthesia. Diagnosis of small fiber neuropathy is determined primarily by the history and physical exam, but functional neurophysiologic testing and skin biopsy evaluation of intraepidermal nerve fiber density can provide diagnostic confirmation. Management of small fiber neuropathy depends on the underlying etiology with concurrent treatment of associated neuropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
138
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(150 citation statements)
references
References 52 publications
0
138
0
5
Order By: Relevance
“…SFN involves small, narrow-diameter myelinated (Ad) and unmyelinated (C) nerve fibres that are the neurological structures responsible for conveying cold and nociceptive input (Ad fibres), innocuous warm and cold sensations, as well as high threshold mechanical, thermal and chemical stimuli (C fibres) [29].…”
Section: Neuropathic Painmentioning
confidence: 99%
“…SFN involves small, narrow-diameter myelinated (Ad) and unmyelinated (C) nerve fibres that are the neurological structures responsible for conveying cold and nociceptive input (Ad fibres), innocuous warm and cold sensations, as well as high threshold mechanical, thermal and chemical stimuli (C fibres) [29].…”
Section: Neuropathic Painmentioning
confidence: 99%
“…We, and others, have recently shown that FM is highly associated with findings of small fiber neuropathy (SFN), a lesion frequently accompanied by severe peripheral pain (1,2). Such a SFN is, therefore, an attractive candidate to serve as one of the peripheral nociceptive generators capable of maintaining the putative central (brain and spinal cord) sensitization thought to be integral to the production of FM painful symptomatology (3).…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of only large fiber function in DM patients is the main limitation in conventional nerve conduction stud-ies. Firstly, diagnosis of small fiber neuropathy is determined by history and physical exams, and then functional neurophysiological testing and skin biopsy evaluation can provide diagnostic confirmation of the disease (Hovaguimian and Gibbons 2011).…”
Section: Introductionmentioning
confidence: 99%